Sistem Aplikasi Surat Masuk dan Surat Keluar Pada Kantor Badan Pusat Statistik Kabupaten Nabire Papua Tengah Berbasis Web - Nilam Tayang; Ester Ayuk Pusvita; Arief Rahman Hakim (STMIK Pesat Nabire, 2023)
This incoming and outgoing mail management application is designed to help simplify the work of agenda staff, where mail management is the daily work of agenda staff in connection with office activities. Incoming mail management includes receiving incoming mail, checking it, recording it in the mailbox and filing it. Meanwhile, outgoing mail is managed from drafting to sending. The working system of this application is divided into two parts, namely incoming mail and outgoing mail. For incoming mail agenda, just record the date of recording, letter number, letter code, letter date, letter source. In the outgoing letter, the concept of a cover letter is given in the form of a column, after completion it will automatically enter the outgoing letter agenda, and the agenda staff does not need to record it again in the outgoing letter book.